The best pairt of our play, Part two essays presented to John J. McGavin - Carpenter, Sarah; King, Pamela M.; Twycross, Meg; Walker, Greg; McGavin, John J. (D.S. Brewer, 2017)
Medieval English Theatre is the premier journal in early theatre studies. Its name belies its wide range of interest: it publishes articles on theatre and pageantry from across the British Isles up to the opening of the London playhouses and the suppression of the civic mystery cycles, and also includes contributions on European and Latin drama, together with analyses of modern survivals orequivalents, and of research productions of medieval plays. This volume comprises the second half of the Festschrift presented to John J. McGavin (of which volume 27 is the first); its essays reflect and honour many of his interests. The subjects addressed include ceremonial (a coronation and a grand funeral), audience reception and spectatorship of many kinds, Welsh drama, the role of womenin the production of libels, and the structure of didactic dialogue plays. A special addition is the late David Mills' last essay, on the Abraham Sacrifiant of Théodore Bèze. Contributors: Mishtooni Bose, Elisabeth Dutton, Alice Hunt, Pamela M. King, David N. Klausner, David Mills, Sue Niebrzydowski, Nadia Thérèse van Pelt, Charlotte Steenbrugge, Eila Williamson
Title from publisher's bibliographic system (viewed on 21 Apr 2017)
Keywords: Geschichte; Theater / England / History / Medieval, 500-1500; English drama / To 1500 / History and criticism; Festschrift